HPV-16 targeted DNA vaccine expression: The role of purification - Almeida, Ana Margarida (2020)
DNA vaccines have come to light in the last decades as an alternative method to prevent many infectious diseases, but they can also be used for the treatment of specific diseases, such as cervical cancer caused by Human Papillomavirus (HPV). This virus produces E6 and E7 oncoproteins, which alter the cell cycle regulation and can interfere with the DNA repairing system. These features can ultimately lead to the progression of cervical cancer, after cell infection by HPV. Thus, the development of a DNA vaccine targeting both proteins arises as an interesting option in the treatment of this pathology. Nonetheless, before evaluating its therapeutic potential, the purity levels of a biopharmaceutical must meet the regulatory agency specifications. Previously, our research group successfully purified the supercoiled isoform of the recombinant HPV-16 E6/E7 DNA vaccine with virtual 100% purity by affinity chromatography. The present work was designed to evaluate the effect that pDNA sample purity levels may exert in the expression of a target protein. Thus, in vitro studies were performed to assess the vaccine ability to produce the target proteins and to compare the expression efficiency between the pDNA sample obtained by affinity chromatography, which only presents the sc isoform and fulfils the regulatory agency recommendations, and the same DNA vaccine retrieved by a commercial purification kit, which contains different pDNA isoforms. Our achievements suggest that the E6/E7 DNA vaccine purified by affinity chromatography promotes higher E6 and E7 mRNA and protein expression levels than the DNA vaccine purified with the commercial kit. Overall, these results underline the importance that a purification strategy may present in the therapeutic outcome of recombinant DNA vaccines, envisaging their further application as biopharmaceuticals. © 2018 American Institute of Chemical Engineers Biotechnol. Prog., 34:546-551, 2018.